(untitled) (Perner’s Contacts, 2014)
Railway line capacity is influenced by several factors. Type of interlocking and safety system is one of them. Railway line capacity can be improved by reconstruction, eventually by upgrading of the interlocking and safety systém. In this paper, developing and construction of simulation model of automatic block is described. Automatic block is type of the interlocking and safety system.